Design of a puncture-resistant composite shell comprising a non-Newtonian core. (May 2018) - Cecchini, Federico; Cherubini, Valeria; Sadaf, Mahrukh; Fabbrocino, Francesco; Nanni, Francesca
Abstract: Puncture resistance has become one of the most requested safety features, not only for protective garments such as stab vests, but also for safety shoes and gloves. Currently, this characteristic is highly demanded in the tyre industry. Conventional protective solutions, such as metallic plates and composite inserts prove to be either bulky or ineffective. The main objective of this work is the design and validation of a novel insert resistant to puncture. This composite insert consisted of a sandwich material with shear-thickening fluid interposed as the core. The dilatancy (shear-thickening) is time-independent rheological behaviour exhibited by some non-Newtonian fluids. These fluids manifest a surge in the apparent viscosity with an increase in the shear rate. In the first part of this work, a comparison between the rheological performance of different shear-thickening fluids (STFs) based on nanosilica dispersed in glycols is presented. This analysis attempts to investigate the combinations of fillers and carriers with the highest energy-absorbing capabilities among various glycol-based colloidal STFs. In the second part, the influence of the composition of the STF on its rheological properties is analyzed statistically. Finally, the puncture resistance of a composite system obtained by encapsulating the previously manufactured shear-thickening fluids in a polymeric shell is analyzed by means of a high-speed puncture test. This test was performed on the mockup of a tyre tread containing the best performing STF. The results showed that the use of the STF core increased the resistance to puncture by 20% as compared to the same volume of tyre tread material. Furthermore, the STF hermetically sealed the pierced sample, even when the tyre mockup was inflated at high internal pressure. Highlights: Optimization of the impact mitigation capabilities of dilatant fluids. D.O.E. analysis of prepared shear-thickening fluids. High-speed puncture test of component made with the best performing dilatants. Design of a novel tyre tread with increased stab resistance and with self-sealing capabilities.